Clinical utility of dermatoscopy in identifying cutaneous myiasis complicating pemphigus vulgaris lesions - Mohammed Asif Qureshi; Rabindra Kumar Yadav; Sonu Kumari Agrawal (Wolters Kluwer Medknow Publications, 2024)
A teenage girl with pemphigus vulgaris (PV) and abetalipoproteinemia experienced an acute PV flare and wound myiasis on her right thigh. Dermatoscopy aided in larval identification as Phormia regina. Treatment included dexamethasone, oral prednisolone, turpentine oil flushes, and larval removal. At the 4-week follow-up, disease activity was controlled, and Magnetic Resonance Imaging (MRI) showed no larvae. This rare case highlighted the co-occurrence of wound myiasis and PV, likely due to poor living conditions. Dermatoscopy was crucial for larval identification, and turpentine oil flushes facilitated larval removal. Ethanol, chloroform spray, and ivermectin are also effective myiasis treatments.